2021
DOI: 10.3390/jmse9091014
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Behavior of Calcareous Sand from the South China Sea

Abstract: This study examines the cyclic behavior of calcareous sand obtained from the South China Sea. A series of undrained cyclic triaxial tests were performed on the calcareous sand with various relative densities, cyclic stress ratios, and effective confining pressures. The test results show that whereas the effective confining pressure exhibited a small influence on the cyclic behavior of the calcareous sand, the effect of changes in CSR and relative density was notable. Due to its angular nature, the liquefaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Calcareous sand, abundant in the South China Sea and originating from marine organisms like corals and shells, mainly consists of insoluble carbonates, particularly calcium carbonate [1][2][3]. Its extensive utilization as a construction filler in island development encompasses a variety of applications, including foundations [4], roadbeds [5], and airport runways [6].…”
Section: Introductionmentioning
confidence: 99%
“…Calcareous sand, abundant in the South China Sea and originating from marine organisms like corals and shells, mainly consists of insoluble carbonates, particularly calcium carbonate [1][2][3]. Its extensive utilization as a construction filler in island development encompasses a variety of applications, including foundations [4], roadbeds [5], and airport runways [6].…”
Section: Introductionmentioning
confidence: 99%
“…He et al [9] investigated the resilient modulus response of coral sand from the South China Sea under cyclic loading and established a new prediction model to predict the resilient modulus of coral sand in the whole stress interval. Liu et al [10] investigated the cyclic behavior of calcareous sand from the South China Sea through a series of undrained cyclic triaxial tests and found that cyclic stress ratios and relative density had a notable effect on the cyclic behavior of calcareous sand, which had higher liquefaction resistance than silica sand due to its angular nature. Ma et al [11] presented the results of a multi-stage strain-controlled undrained cyclic shear test on saturated coral sand and proposed a new index to modify the prediction model of the maximum shear modulus and reference shear strain under different consolidation conditions, which shows an excellent prediction of shear modulus with a deviation within ±10%.…”
Section: Introductionmentioning
confidence: 99%
“…The promotion of the Hainan free trade port policy has attracted the attention of the state toward the construction and development of the South China Sea islands and reefs. Calcareous sand, which is widely distributed in the South China Sea, is mainly composed of coral debris, submarine limestone, and marine biological debris with a CaCO 3 content of more than 50% [1,2]. Calcareous sand is not conducive to direct application in engineering because of the irregular shape, large porosity, low bearing capacity, and fragile engineering characteristics of the sand particles [3,4].…”
Section: Introductionmentioning
confidence: 99%